DILEMA ETIS DALAM SATUAN PENGAWASAN INTERN (SPI) (Studi Kasus Pada Universitas Trunojoyo Madura) - Rahmat Zuhdi (InFestasi, 2012)
The importance of the internal control in the public sector has been responded by the Indonesian Government by enacting the Government Law (PP) No.60/2008 about the Government’s Internal Control System. Meanwhile, in responds to that law, the Ministry of Education ratified the Regulation of Ministry of Education (Permendiknas) No. 16/2009 regarding the Internal Control in this Ministry. Furthermore, Trunojoyo University followed up the Regulation by enacting the Rector Regulation (SK Rektor) No. 030/H46/2011. This Rector Regulation clarifies the member of Internal Auditor as well as their roles and responsibilities in the University as well as the Faculty. However, this regulation generates dilemma for the Internal Auditor itself. The Internal Auditor members find themselves at the cross-purposes with their roles at Trunojoyo University. The internal auditor members play dual roles as a internal auditor and lecturer. It means that, as a lecturer, internal auditor might examine their collages, or their workplace.           The approach of this study is a case study by analyzing documents including letter of decision (SK) and others documents related to this study. This approach was seen as the most appropriate method to comprehensively explain the social situation of ethic dilemma faced by internal auditor members.     The study results suggested that conflict of interest exposes due to the dual roles of Internal Auditor members. These dual roles can jeopardize the independency and the objectivity of internal auditor duties.